Birobidzhan: historical transformations of trade spaces in the satellite city - Ju. V. Ordynskaya; L. G. Dyachkova (Архитектура, строительство, транспорт)
A number of studies are devoted to the urban development of settlements in the Far East, but they do not consider trade spaces as structureforming spaces, whereas they often form the framework of the city. After studying the cadastral maps of Birobidzhan, topographic survey materials, online maps and other documents, we identified five historical periods of formation of outdoor trade spaces in Birobidzhan and their architectural and planning features. The first stage was 1928-1933: the period of free development of the territory, when the trade environment was an instrument of social adaptation of the developed space. The second was 1932-1937, when professional architects were invited to the planning and development of the city, and the market square received its official status. The third stage was 1937-1990: the period of planned development of the territory, when the planned trade environment was formed. The fourth was in the 1990s: it was the time of post-socialist transformation, the typical feature of which was self-organization of market space, the trade street reflected the crisis phenomena in the urban system. The fifth stage lasts from 2000 to the present and includes reorganization of trade spaces: demolition of old pavilions and stalls in the Central Market area, emergence of seasonal fairs as a new form of open trade in the city, concentration of small open trade spaces near the existing markets at the same time with separate functioning of large shopping centres that close the adjacent territories from street trade. The comprehensive programme for the implementation of the concept "Compact competitive city with jewish colour on the border with China" (master plan of Birobidzhan until 2030) envisages, among other things, the renovation of trade spaces. It should take into account trade as a social phenomenon.